INFORMASI ASIMETRIS DALAM TRANSMISI HARGA GABAH DAN HARGA BERAS - Agus Hermawan; Sarjana Sarjana; Miranti D. Pertiwi; Indri Ambarsari (JURNAL LITBANG PROVINSI JAWA TENGAH, 2008)
Prices transmission study between paddy grain and rice aimed to find out whether the rice price formation due to the price shock in paddy grain was symetric or asymetric. Weekly data of paddy grain and rice prices from Grobogan, Pati, and Wonogiri Districts, as paddy production center and Semarang as rice demand area, were analyzed. Data were taken from Central Java Food Crops Services and covering a period from January 2000 to April 2003. Results showed that paddy grain and rice prices had the same fluctuation pattern. Paddy grain price shock tend to be transmited smoothly to rice price in paddy production center, but markets respond increasing shock faster than decreasing shock. Asymetric information was mostly found in Semarang City, in which rice price moved diverse from paddy grain price shock in Grobogan, Pati, and Wonogiri Districts